Mapping scientific output in Information Science: a bibliometric study on 'Absorptive Capacity' - Nunes, Ana Camila Nobre Xavier; Oliveira, Silvia Amélia Fonseca de; Werlang, Nathália Berger (Informação em Pauta, 2025)
This article aims to map Brazilian scientific production on the topic of "Absorptive Capacity" within the field of Information Science. It is a descriptive study, with a quantitative approach, grounded in bibliometric methods. The analysis was conducted using the BRAPCI and SciELO databases, based on the following search terms: “Capacidade Absortiva,” “Ciência da Informação,” “Gestão da Informação,” and “Gestão do Conhecimento.”, also in English. The data allowed for: (a) identifying the journals with the highest number of publications; (b) mapping the most frequent keywords; (c) verifying the years with the highest publication incidence; and (d) identifying the most cited authors. The results indicate that Absorptive Capacity remains underexplored in the context of Information Science in Brazil, despite its presence in various other fields of knowledge, reinforcing its multidisciplinary nature.